Defining the genome structure of ‘tongil’ rice, an important cultivar in the korean “green revolution - Kim, Backki; Kim, Dong-Gwan; Lee, Gileung; Seo, Jeonghwan; Choi, Ik-Young; Choi, Beom-Soon; Yang, Tae-Jin; Kim, Kwang Soo; Lee, Joohyun; Chin, Joong Hyoun; Koh, Hee-Jong (Springer, 2014)
Tongil (IR667-98-1-2) rice, developed in 1972, is a high-yield rice variety derived from a three-way cross between indica and japonica varieties. Tongil contributed to the self-sufficiency of staple food production in Korea during a period known as the `Korean Green Revolution'. We analyzed the nucleotide-level genome structure of Tongil rice and compared it to those of the parental varieties. Results A total of 17.3 billion Illumina Hiseq reads, 47× genome coverage, were generated for Tongil rice. Three parental accessions of Tongil rice, two indica types and one japonica type, were also sequenced at approximately 30x genome coverage. A total of 2,149,991 SNPs were detected between Tongil and Nipponbare varieties. The average SNP frequency of Tongil was 5.77 per kb. Genome composition was determined based on SNP data by comparing Tongil with three parental genome sequences using the sliding window approach. Analyses revealed that 91.8% of the Tongil genome originated from the indica parents and 7.9% from the japonica parent. Copy numbers of SSR motifs, ORF gene distribution throughout the whole genome, gene ontology (GO) annotation, and some yield-related QTLs or gene locations were also comparatively analyzed between Tongil and parental varieties using sequence-based tools. Each genetic factor was transferred from the parents into Tongil rice in amounts that were in proportion to the whole genome composition. Tongil was derived from a three-way cross among two indica and one japonica varieties. Defining the genome structure of Tongil rice demonstrates that the Tongil genome is derived primarily from the indica genome with a small proportion of japonica genome introgression. Comparative gene distribution, SSR, GO, and yield-related gene analysis support the finding that the Tongil genome is primarily made up of the indica genome.